1973
DOI: 10.1192/bjp.123.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Brain Disconnection and Schizophrenia

Abstract: The concept of brain disconnection derives from work in which the two cerebral hemispheres are surgically separated by division of the corpus callosum. The patient behaves as if his two half-brains function to some degree independently. The syndrome of brain disconnection is exemplified by such split-brain cases (Geschwind, 1965). Neither hemisphere shows an awareness of the functions of the other, and there is a marked failure to cross-match stimuli across the midline of the body. The integrity of the corpus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(68 citation statements)
references
References 3 publications
6
62
0
Order By: Relevance
“…Following the initial observations of Beaumont and Dimond, 125 patients have often been reported to be impaired in matching stimuli presented separately to the right and the left hemisphere. This suggests that 73 by stating that 'Experiments requiring integration of stimuli presented across the visual field, which presumably relies on an efficient CC, show impairment in schizophrenics, and this is especially so for nonverbal stimuli'.…”
Section: Electrophysiological Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Following the initial observations of Beaumont and Dimond, 125 patients have often been reported to be impaired in matching stimuli presented separately to the right and the left hemisphere. This suggests that 73 by stating that 'Experiments requiring integration of stimuli presented across the visual field, which presumably relies on an efficient CC, show impairment in schizophrenics, and this is especially so for nonverbal stimuli'.…”
Section: Electrophysiological Studiesmentioning
confidence: 97%
“…Synapses may fail to be eliminated in development, specifically during adolescenceFthe hyperconnectivity hypothesis 12 For, alternatively, too many synapses are eliminatedFthe hypoconnectivity hypothesis. 13,14 Both hypotheses seem to be directly testable by neuropathological investigations. Nevertheless, they grossly oversimplify the structural-functional relations that characterize cortical connections.…”
Section: Connectivism and Schizophreniamentioning
confidence: 99%
“…36 Beaumont and Dimond reported impaired interhemispheric transfer in patients with schizophrenia. 37 Neuropathological studies have found increased neuronal density and abnormalities in the pyramidal neurons of Layer III of prefrontal cortex. 38,39 These neurons play a key role in cortical-cortical connectivity, suggesting that cortical connectivity may be altered in schizophrenia.…”
Section: Schizophreniamentioning
confidence: 99%
“…EEG investigations showed abnormal activity of the right side of the brain in children at high risk for schizophrenia and schizophrenics, especially in tempera-parietal leads (Itil et al 1974;Giannitrapani and Kayton 1974). Beaumont and Dimond (1973) found decreased left hemisphere performance on a letter matching task in schizophrenic subjects when compared to normal controls, and decreased right hemisphere performance for digit matching when compared to psychiatric controls: the authors felt that the most direct explanation of their results, is that in schizophrenia the 2 cerebral hemispheres are partially disconnected, and that this reflects some change in the efficiency of the corpus callosum. *Wechsler Adult Intelligence Scale -123 - 4.2.ii.c.…”
Section: Drugs Particularly Implicated (Seementioning
confidence: 96%